OP13 CD8b low T cells are a prominent, functionally distinct population in chronic hepatitis B infection. (6th September 2011) - Marrinan, E; Walker, L; Barnes, E; Klenerman, P
Abstract : Introduction: The failure of antigen-specific CD8 T cells is a well recognised feature of chronic hepatitis B (HBV) infection, however the bulk CD8 T cell population is also characterised by low expression of CD28 and poor IL-2 production and proliferation capacity (Das, Hoare et al 2008). We have previously observed a prominent CD8 T cell population in chronic HBV to be CD8b low (Walker, Kang et al ) - this is most obvious in the cells which lack expression of CD161 (a molecule associated with liver homing). The relationship of these two observations has not previously been explored. Such changes may represent infection induced immune exhaustion or an acquired tolerance mechanism, which is breached during flares in disease activity. Both scenarios have important implications either for development of immunotherapy for viral clearance or treatment for prevention of disease progression. Aim: The aim of this study was to further characterise the phenotypic and functional features of the bulk CD8 T cell population in chronic HBV infection and the relationship of CD28 low CD8+ and CD161-CD8b low T cell populations. Method: Peripheral blood mononucleocytes were obtained from patients with eAg+ve chronic HBV (n=6), eAg−ve chronic HBV (n=12), chronic hepatitis C (HCV) genotype 1 (n=5) and healthy controls (n=8). All patients were treatment naïve and had stable disease. FACS analysis was performed on both cell surface antibody staining using a panel of activation/exhaustion markers (CD25, CD38, CD69, HLA-DR, PD-1, CD8b) and intracellular cytokine staining following PMA/ionomycin stimulation. CD8b high T cells were freshly isolated from health controls and sorted using magnetic beads, prior to culture in a variety of conditions and subsequent FACS analysis. Results: In chronic HBV infection, regardless of eAg status, CD161-CD8b low T cells express significantly lower CD28 (eAg+ve p=0.005, eAg−ve p=0.0001) and significantly higher HLA-DR (eAg+ve p=0.002, eAg−ve p=0.009) than their CD161-CD8b high counterparts. The CD161-CD8b low CD28 low HLA-DR high population represents a mean of 38% of total CD8 T cells in chronic HBV. The CD161-CD8b low CD28 low HLA-DR high population produce significantly more IFN-g on stimulation with PMA/ionomycin than their CD8b high CD28 high HLA-DR high counterparts (p<0.0001). No difference was observed in IL-2 production. In addition we are able to demonstrate ready transition of sorted CD161-CD8b high to CD161-CD8b low T cells from healthy controls cultured overnight in culture media alone, which provides an insight into the potential mechanisms involved in the generation of this population and an in-vitro model for use in further study. Conclusion: CD161-CD8b low CD28 low HLA-DR high T cells are a functionally distinct, prominent T cell population in chronic HBV infection that are likely to profoundly influence the immune environment with important implications for the development of immunotherapy and treatment. The absence of this T cell subset in chronic HCV indicates a disease-specific rather than liver-related effect.